Сучасні соціально-економічні аспекти явища overtourism в Україні та світі - Пархоменко О.; Parkhomenko O.; Щука Галина; Scsuka Halina; Shchuka Halyna; Ковальська Леся; Kovalska Lesia (ФОП «Фенікс», 2025)
Резюме. У статті розглянуто overtourism як багатогранне соціально-економічне явище, що сприяє економічному розвитку регіонів та породжує значні виклики для навколишнього середовища, інфраструктури та соціокультурного середовища. Проаналізовано передумови, прояви та наслідки overtourism у глобальному та національному контексті. Методологічною основою дослідження стали загальнонаукові методи аналізу, синтезу, порівняння та систематизації, а також статистичні дані UN Tourism, Державної прикордонної служби України, ДАРТ та органів місцевого самоврядування. Встановлено динаміку туристичних потоків у 2023–2025 рр., виділено ключові дестинації, які зазнають overtourism. Виділено ознаки overtourism. Виокремлено причини та локації цього явища в Україні. Перспективи подальших досліджень полягають у формуванні індикаторів для оцінювання рівня overtourism у національних умовах та розробці механізмів інтегрованого управління туристичними потоками.

Abstract. Overtourism is a unique phenomenon that simultaneously exerts both positive and negative impacts on various aspects of society, the environment, and the economy. The article explores the emergence and intensification of overtourism in different parts of the world and identifies key trends observed globally and in Ukraine. Based on statistical data from UN Tourism and national institutions, the study highlights a steady post-pandemic increase in international tourist flows, especially in the Asia-Pacific region, the Middle East, and Europe. Particular attention is paid to the negative consequences of overtourism, including increased pressure on local infrastructure, inflation in housing and services, changes in community structure, and degradation of the natural and cultural environment. The research identifies manifestations of overtourism in Ukraine during the war, particularly in cities like Lviv, Uzhhorod, and Uman, and in natural tourist destinations such as the Carpathians and national parks. The study outlines economic indicators—such as rising tax revenues, tourist fees, and prices during peak seasons—that signal the growing scale of the phenomenon. Specific attention is given to the issue of waste management in overloaded destinations, as illustrated by the cases of Yaremche, Kosiv, and the Synevyr and Halych National Nature Parks. The article suggests regulatory and educational measures to mitigate the effects of overtourism in the post-war period, including limiting visitor numbers in peak seasons, promoting lesser-known destinations, and fostering environmental awareness. The scientific novelty of the research lies in the identification of overtourism as an emerging phenomenon in Ukraine under war conditions and the substantiation of strategic tools for its management. The practical significance of the findings is evident in the potential use of proposed solutions by local authorities, tourism managers, and environmental institutions to ensure the sustainable development of tourism.
Modern socio-economic aspects of the overtourism phenomenon in Ukraine and the world
Keywords: overtourism; туристичне навантаження; туристичні потоки; внутрішній туризм; туристичний збір